Pelaksanaan Kerja Sama antara Penanam Modal dengan Badan Usaha Milik Daerah di Kabupaten Kutai Kartanegara - Karni, Andi Waisal; Rahman, Sufirman; Zainuddin, Zainuddin (Amsir Law Journal, 2023)
Government involvement in the economic field, by making agreements or business contracts cannot be separated from the government’s aim to improve the welfare of the people, where the state plays a very important role in the economic field and directly intervenes in the course of the economy. This research uses empirical law, namely a legal research method that uses empirical facts taken from human behaviour related to cooperation agreements between investors and Regional Owned Enterprises or BUMD in Kutai Kartanegara, using qualitative research taken from field data journals, books and the internet as references then analyzed by the author. Kutai Kartanegara Regency’s investment form consists of three sectors, namely the primary sector, secondary sector and tertiary sector. Kutai Kartanegara Regency has been able to attract foreign and domestic investment in the mining sector dominantly compared to other sectors. This success is inseparable from the support of strategic government policies both nationally and regionally so as to create a conducive investment climate and encourage an increase in local revenue. ___ Referensi Buku dengan penulis: Ida, B. R. S. (2006). Kerangka Hukum Kebijakan Investasi Langsung di Indonesia. Bogor: Ghalia Indonesia. Suparji. (2010). Pengaturan Penanaman Modal di Indonesia. Jakarta: Universitas Al-Azhar Indonesia. Artikel jurnal: Ainiyyah, G. R. (2022). Badan Usaha Milik Daerah (BUMD) yang belum berubah Status menjadi Perumda atau Perseroda. Notary Law Journal, 1(2), 176-203. Ansari, M. I. (2020). Omnibus Law Untuk Menata Regulasi Penanaman Modal. Jurnal Rechts Vinding: Media Pembinaan Hukum Nasional, 9(1), 71-90. Djumardin, D., & Kusuma, R. (2015). Penyertaan Modal “Pemda” Pada Badan Usaha Milik Daerah (BUMD) (Kajian Terhadap Penyertaan Modal Pemerintah Pada PT.DMB Dalam Divestasi Saham PT.Newmont Nusa Tenggara). Jurnal Hukum JATISWARA, 30(1), 103-114. Hidayah, A. (2018). Landasan Filosofis dan Asas-Asas Dalam Hukum Penanaman Modal di Indonesia. Solusi, 16(3), 216-226. Muryanto, Y. T. (2014). Model Pengelolaan Badan Usaha Milik Daerah (BUMD) dalam Rangka Mewujudkan Good Corporate Governance. Yustisia Jurnal Hukum, 3(1), 125-134. Paulin, S. T. (2021). Perkembangan Joint Venture Company dalam Pembangunan Infrastruktur Ketenagalistrikan. Jurnal Hukum To-Ra: Hukum untuk Mengatur dan Melindungi Masyarakat, 7(2), 267-282. Purwanda, S., & Wulandari, A. S. R. (2023). Socio-Legal Studies: Methodical Implications of Legal Development in Indonesia. Al-'Adl, 16(2), 152-163. Ramadhan, M. S., & Laily, Y. (2018). Analisis Hukum Perjanjian Kerja Sama Investasi antara Persekutuan Komanditer dan Investor Asing menurut Hukum Investasi di Indonesia. Lex Librum: Jurnal Ilmu Hukum, 5(1), 771-780. Rizky, R. L., Agustin, G., & Mukhlis, I. (2016). Pengaruh Penanaman Modal Asing, Penanaman Modal Dalam Negeri dan Belanja Modal Terhadap Pertumbuhan Ekonomi Provinsi di Indonesia. Jurnal Ekonomi dan Studi Pembangunan, 8(1), 9-16. World Wide Web: Marpaung, D. (2021). Ketentuan Penanaman Modal berdasarkan Bidang Usaha Pasca UU Cipta Kerja. Tersedia secara daring dari: https://www.dhp-lawfirm.com/ketentuan-penanaman-modal-berdasarkan-bidang-usaha-pasca-uu-cipta-kerja/ .